Meningkatkan Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Circuit Learning Pada Pembelajaran Tematik : Indonesia - sholahudin din; Hidayah; Anggi Fitri (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to determine the use of the circuit learning model in the thematic learning of class III students of Madrasah Ibtidaiyah Muhajirin Jambi City. This research is a classroom action research (PTK) which is descriptive qualitative using a qualitative approach reinforced by a quantitative approach. The object of research is the use of the circuit learning model to improve thematic learning outcomes with the theme of five sub-themes and the circuit learning model. This research was conducted in two cycles through four stages, namely: (1) planning. (2) implementation, (3) observation, and (4) reflection. Data obtained through observation, interviews, tests, or evaluation of learning outcomes and documentation. Data analysis was performed using learning outcomes with tests in cycle I and cycle II. In the pre-cycle I approach, it shows that all learning activities are not well enough to be carried out by students even though there has been an increase in cycle I and are still in the low predicate because the average percentage of activities is still below 72%, cycle II has shown satisfactory results both from the activity. student learning has been in the predicate sufficient, good, and very good while student learning outcomes have reached an average of 80% with a classical percentage of 80% means that corrective action for the learning process has met the criteria.